2012
DOI: 10.1002/htj.21002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of mixed convection heat transfer in a horizontal channel with an open cavity containing a heated hollow cylinder

Abstract: The objective of this paper is to numerically investigate the mixed convective flow and heat transfer controlled by a heated hollow cylinder inside an open cavity attached with a horizontal channel. All the boundaries of the channel and cavity are perfectly insulated while the inner surface of the cylinder is heated uniformly by heat flux q. The equations of conservation of mass, momentum, and energy were solved using adequate boundary conditions by Galarkin's weighted residual finite element technique. The so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…They concluded that the heat transfer rate was increased by increasing the Reynolds number for fixed values of the Richardson number. Extra references about the mixed convection in an open enclosure‐channel assembly can be found in References . To the authors’ best knowledge, there is a lack of research dealing with the mixed convection in an open enclosure‐channel assembly, especially when the geometry of the enclosure is considered complicated.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the heat transfer rate was increased by increasing the Reynolds number for fixed values of the Richardson number. Extra references about the mixed convection in an open enclosure‐channel assembly can be found in References . To the authors’ best knowledge, there is a lack of research dealing with the mixed convection in an open enclosure‐channel assembly, especially when the geometry of the enclosure is considered complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Independence test of grid and time-step intervals for Re=550, D=0.2 and S=0.2 Comparison of area-averaged Nusselt number of numerical simulation with empirical correlation(9) and other researches…”
mentioning
confidence: 93%
“…The distributions of streamlines, isotherms and heat transfer coefficient were reported for wide ranges of the parameters, including Reynolds number, Richardson number, Prandtl number and some physical parameters. Rahman et al [9] numerically investigated mixed convective flow and heat transfer of a heated hollow cylinder (uniform heat flux) inside an open cavity attached with a horizontal channel for 10 3 <Ra<10 5 , 0.7<Pr<7 and ratio of solid to fluid thermal conductivities from 0.2 to 50. Mamun et al [10] solved the mixed convection heat transfer characteristics within a ventilated square cavity with a heated hollow cylinder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These orifices have different widths. Moreover, there are other works on mixed convection in an enclosure under different situations 20‐26 …”
Section: Introductionmentioning
confidence: 99%